Report of the 2nd Annual General Meeting of ENETWILD 5‐6th October 2021. Issue 12 (20th December 2021) - ,; Pascual, R; Acevedo, P; Apollonio, M; Blanco‐Aguiar, JA; Body, G; Casaer, J; Ferroglio, E; Gomez Molina, A; Illanas, S; Jansen, P; Keuling, O; et al.
Abstract: The 2 nd ENETWILD Annual General Meeting took place on 5‐6 th October 2021, bringing together experts, stakeholders and ENETWILD collaborators in online workshop discussions. First, workshop discussions contributed to the analysis and proposal of approaches for a harmonized European‐wide wildlife monitoring framework able of sustaining coordinated decision‐making. Secondly, participants identified the key challenges that managers face in making decisions for wildlife in Europe and data needs for policies. Finally, we illustrated these challenges with the case of wild boar as a model species widely distributed across Europe. Inputs from the participants were collated into a plan of proposed steps and objectives for the mid‐term (5‐year time frame) to achieve progress on harmonised, coordinated, and integrated wildlife monitoring at the European level, which requires the contribution of experts from the early stages.. Specific proposed actions include the creation of a trans‐disciplinary authority at the European level, effective points of reference for data collection and sharing at different administrative levels and countries, a standing committee to coordinate and exchange experience and capacities on data collection between countries, and expert groups for problem solving, with proper EU financial support, establishing regular policy meetings. . To provide useful results, wildlife monitoring must ensure proper design and data analysis for subsequent science‐based management and best allocation of management resources. The 'Observatory' approach (a representative network of intensively monitored sites) can provide long‐term systematic and representative insights, normally more feasible for comparative studies, providing less biases and support for decision‐making. For international decision‐making by wildlife managers and politicians based on scientific knowledge and interdisciplinary research, experts should define the foundations of a common European wildlife decision‐making framework (inter‐institutional and inter‐sectorial). The development of a European legislation on wildlife management may represent an opportunity for addressing the abovementioned steps, identifying data priorities matching the needs of the various European Directorates, Agencies, and monitoring frameworks.